Kemampuan Guru PAI dalam Pengembangan Materi Ajar Pendidikan Agama Islam di MAS Nurul Furqoon Binjai - Hadi Sufyan; Mariyati Mariyati; Sri Rahmayani Manalu; Siti Halimah (Tarbiatuna: Journal of Islamic Education Studies, 2024)
The Ability of PAI Teachers in Developing Teaching Materials for Islamic Religious Education at MAS Nurul Furqoon Binjai. The purpose of this study was to determine the development of teaching materials for Islamic Religious Education at Mas Nurul Furqoon. This study uses a qualitative approach with the CIPP technique, then the instruments used are observation, interviews, and documentation. The results of the study stated that the development of teaching materials is very important for learning activities in the classroom, because the development of teaching materials is able to make students more easily understand in understanding the material and are more active in knowing more about the material being taught. This research shows that PAI teachers at Madrasah Aliyah Nurul Furqoon Binjai have good competence in the field of PAI and seek to continuously improve their abilities through training and supervision conducted by the school. This shows the school's commitment to ensure that PAI teachers remain professional and ready to face the times in the world of education. The conclusion of this study is that the teacher's ability to develop teaching materials for Islamic Religious Education at Madrasah Aliyah Nurul Furqoon Binjai is quite good. PAI teachers at the school have good competence in various aspects of learning and are constantly working to improve their skills. In the context of PAI learning, these teachers are able to create positive and effective learning experiences for students, as well as contribute to the formation of students' personalities and morals in accordance with Islamic teachings. Keywords: Teacher Ability, Material Development, Teaching Materials, CIPP.